The Transgenerational Transmission of Trauma: The Effects of Maternal PTSD in Mother-Infant Interactions - Dozio, Elisabetta; Feldman, Marion; Bizouerne, Cécile; Drain, Elise; Laroche Joubert, Mathilde; Mansouri, Malika; Moro, Marie Rose; Ouss, Lisa (Frontiers in Psychiatry, 2020)
The objective of the study was to examine the process of mother to infant trauma transmission among traumatised mothers in humanitarian contexts. We investigated the impact of mothers’ posttraumatic stress disorder symptoms on the quality of the dyadic interaction by conducting a microanalysis of mother-infant interactions at specific moments when trauma was recalled, compared to more neutral moments. 24 mother-infant dyadic interactions of traumatised mothers and children aged from 1.5 to 30 months Central Africa, Chad and Cameroon were videotaped during three sequences: a neutral initial session (baseline) exploring mothers’ representations of the infant and of their bonding; a second sequence, “the traumatic narration”, in which mothers were asked to talk about the difficult events they had experienced; and a third sequence focusing on a neutral subject. Three minutes of each sequence were coded through a specific grid for microanalysis (based on the scales developed at Bobigny Faculty of Medicine and the work of Beebe), according to different communication modalities, (touch, visual and vocal) for both the mother and the child. Impact of traumatic event (IES-R), the level of depression and anxiety (HAD) were investigated in order to have a holistic understanding of the trauma transmission mechanism. The data analysis highlighted significant differences in mothers, children and their interaction during the “traumatic narration”: mothers touched and looked at the infant less, looked more absent and smiled less, and looked less at the interviewer; infants looked less at the interviewer, and sucked the breast more. The mother-child interaction “infant self-touch - mother looks absent” and “Infant sucks the breast - mother looks absent” occurred more often during the mothers’ traumatic narrations. The “absence” of the mother during trauma recall seems to have repercussions on infants’ behaviour and interaction; infants show coping strategies that are discussed. We found no significant associations between interaction and infant gender and age, the severity of traumatic experience, mothers’ depression and anxiety symptoms, and the country of residence. The results of the microanalysis of interaction can shed light on the fundamental role of intermodal exchanges between mother and infant in trauma transmission during mothers’ trauma reactivation.